2020
DOI: 10.1021/acsnano.0c06190
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Intracellular Redox Balance with Diselenium Nanoparticles for Maximizing Chemotherapy Efficacy on Patient-Derived Xenograft Models

Abstract: Excessive oxidative stress in cancer cells can induce cancer cell death. Anticancer activity and drug resistance of chemotherapy are closely related to the redox state of tumor cells. Herein, five lipophilic Pt(IV) prodrugs were synthesized on the basis of the most widely used anticancer drug cisplatin, whose anticancer efficacy and drug resistance are closely related to the intracellular redox state. Subsequently, a series of cisplatin-sensitive and drug-resistant cell lines as well as three patient-derived p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 52 publications
1
88
0
2
Order By: Relevance
“…3 h, i). Compared with the traditional PDT, a ROS-mediated therapeutic modality [ 47 ], the main advantage of TDT is that the cytotoxic alkyl radicals also can be generated under the hypoxic tumor microenvironment. To prove it, we also detected the in vitro ROS production during ZnPc-mediated PDT under both hypoxic and normoxic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…3 h, i). Compared with the traditional PDT, a ROS-mediated therapeutic modality [ 47 ], the main advantage of TDT is that the cytotoxic alkyl radicals also can be generated under the hypoxic tumor microenvironment. To prove it, we also detected the in vitro ROS production during ZnPc-mediated PDT under both hypoxic and normoxic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The combined and cascaded tailoring would obviously disturb the intratumoral GSH‐ROS balance to induce the apoptosis. [ 27 ] Based on these in vitro experiments, we also detected the TNF‐ α expression (reflecting ROS damage) of the tumors isolated from the orthotopic tumor‐bearing mice post different treatment by Western–Blots method. The results indicated that targeted SO 2 delivery plus a photothermal treatment would lead to the highest ROS injury to the tumor cells (Figure S25B , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Sabe-se que o equilíbrio de oxirredução celular desempena importante papel na regulação comportamental celular, tais quais se resumem em processos fisiopatológicos, como transcrição de genes, transdução de sinal, proliferação, diferenciação, apoptose e necrose são regidos pelo equilíbrio de redox (WEI et al, 2020).…”
Section: Discussionunclassified
“…No entanto, os mecanismos para todas essas estratégias quase dependem da depleção da glutationa (GSH) ou do aumento das espécies reativas de oxigênio (ROS), todavia, poucos sistemas conseguem atingir ambos os efeitos simultaneamente, o que limitaria a amplificação final do estresse oxidativo. Além disso, embora os nanocatalisadores tenham sido amplamente empregados para quebrar o equilíbrio redox, a maioria deles são materiais inorgânicos (WEI et al, 2020).…”
Section: Discussionunclassified